The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/prp2.329
|View full text |Cite
|
Sign up to set email alerts
|

Obeticholic acid, a selective farnesoid X receptor agonist, regulates bile acid homeostasis in sandwich‐cultured human hepatocytes

Abstract: Farnesoid X receptor (FXR) is a master regulator of bile acid homeostasis through transcriptional regulation of genes involved in bile acid synthesis and cellular membrane transport. Impairment of bile acid efflux due to cholangiopathies results in chronic cholestasis leading to abnormal elevation of intrahepatic and systemic bile acid levels. Obeticholic acid (OCA) is a potent and selective FXR agonist that is 100‐fold more potent than the endogenous ligand chenodeoxycholic acid (CDCA). The effects of OCA on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 48 publications
3
47
1
Order By: Relevance
“… FXR activation by OCA has an EC 50 value of approximately 100 nmol/L . Previous studies by the authors utilizing a physiologically relevant cellular model of sandwich‐cultured human hepatocytes (SCHH) demonstrated a significant reduction in endogenous bile acids following 72‐hour incubation of OCA . In the same study, a head‐to‐head comparison confirmed that OCA was 100‐fold more potent than CDCA on FXR.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“… FXR activation by OCA has an EC 50 value of approximately 100 nmol/L . Previous studies by the authors utilizing a physiologically relevant cellular model of sandwich‐cultured human hepatocytes (SCHH) demonstrated a significant reduction in endogenous bile acids following 72‐hour incubation of OCA . In the same study, a head‐to‐head comparison confirmed that OCA was 100‐fold more potent than CDCA on FXR.…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies in SCHH have demonstrated that OCA and CDCA up to 100 μmol/L showed no overt cytotoxicity . To optimize treatment concentration of UDCA, cytotoxicity of increasing concentrations of UDCA (1.0‐1000 μmol/L) was evaluated by morphological and ATP assessments (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations